MODEL INKUIRI: KATALISATOR PENGARUH PEMBELAJARAN FIQH TERHADAP MOTIVASI DAN CAPAIAN BELAJAR SISWA - Edo Ramada; Agus Jatmiko; Sunarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
An in-depth investigation of a study aimed at comprehensively examining the influence of the inquiry learning model on the learning motivation and learning outcomes of tenth-grade students in MA Al-Hikmah Bandar Lampung. Given that student learning motivation and learning outcomes often need improvement, this study examines inquiry as a learning catalyst. The research method used was quantitative with a quasi-experimental approach, involving the measurement of numerical data to analyze the relationship between variables. The population of this study included all tenth-grade students in MA Al-Hikmah Bandar Lampung, with the sample being determined using purposive or cluster random sampling to ensure relevant representation. Quantitative data were collected through test instruments to measure learning outcomes (learning outcomes) and questionnaires to measure student learning motivation. Data analysis was conducted using descriptive and inferential statistical tests, such as the t-test, to compare the group implementing the inquiry model with the control group and to identify the significance of its influence. Previous research has shown that the inquiry model, both guided and media-based, can improve student motivation and learning outcomes in various subjects and educational levels. This study is expected to provide the latest empirical evidence regarding the effectiveness of the inquiry model in increasing motivation and learning achievement of Islamic jurisprudence at the Madrasah Aliyah level, especially at MA Al-Hikmah Bandar Lampung, as well as offering practical implications for the development of more interactive and participatory learning strategies in Islamic religious education.